Environmental Conservation Values in Zawawi Imron's Literature: An Ecosemantic Study - Ismatul Izzah; Darni Darni; Mintowati Mintowati (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2025)
This study aims to uncover environmental conservation messages contained in Zawawi Imron's literary works through an ecosemantic approach. Ecosemantics, as a branch of ecological linguistics, focuses on the relationship between the meaning of language, nature, and culture. Zawawi Imron, a poet known as the